The interpretation of financial statements - Graham, Benjamin; McGolrick, Charles (New York : Harper & Row, 1964)
The book is designed to enable you to read financial statements intelligently. It is also designed either for independent study as an elementary work or as an introduction to a more detailed treatment of the subject- such as security analysis.
"A second revision of the book by Benjamin Graham and Spencer B. Meredith first published in 1937 [under the same title]"
Includes bibliographical reference
hza 29/01/2019
Loans
Keywords: Financial statements